An epidural arteriovenous fistula studied with time-resolved imaging of contrast kinetics (TRICKS) sequence. Issue 6 (December 2016) - Romano, Andrea; Consoli, Arturo; Tari Capone, Francesca; Biraschi, Francesco; Suma, Giacomo; Mangiafico, Salvatore; Bozzao, Alessandro
We describe the use of time-resolved MR angiography in the diagnosis of cervical epidural arteriovenous fistula before final diagnosis and embolization was achieved by digital subtraction angiography. A 42-year-old woman was referred to us because of headache and dizziness, in addition to radiculopathy of the right superior limb. Angiographic examinations documented a direct high-flow arteriovenous fistula between the right vertebral artery and the cervical epidural venous plexus. The point of fistula was located in the upper third of the cervical segment below the C2 arch. Time-resolved MR angiography might add important information in case of suspected arteriovenous fistula, helpful both for therapeutic decisions and follow-up.